Pleomorphic Adenoma of the upper lip - karam, Nasar karam (AL-Kindy College Medical Journal, 2019)
The pleomorphic adenoma is a benign salivary gland tumor, presenting usually in the parotid gland. This case report describes an unusual case of 29 years old female with a single, nodular swelling evident in the upper lip which was diagnosed as pleomorphic adenoma of the minor salivary glands in the upper lip .The lesion measured 1.0 x 1.0 cm in size for 2 years duration cause depression of labial cortical bone apical to lateral and canine teeth. It is characterized by slow growth. Complete excision was performed and the histopathological analysis supported by immunohistochemistry showed pleomorphic adenoma .It did not recur 18 months after operation.